Controllable synthesis of MoS2@TiO2 nanocomposites for visual detection of dopamine secretion with highly-efficient enzymatic activity. Issue 8 (20th March 2023) - Wei, Chonghui; Xie, Xuan; Mou, Yue; Cheng, Shiqi; Yang, Jin; Xue, Kaixin; Yu, Kewei; Lin, Xinru; Zhang, Chunfen; Zhao, Yujie; Luo, Xingyu; Wang, Yilin
Abstract : Facile method and specific reactant mass ratio for nanocomposite synthesis and dopamine detection. Abstract : Dopamine (DA) plays an essential role in dopaminergic neuronal behavior and disease. However, current detection methods for discriminating the secretion of DA are hampered by the limitations of the requirement for bulky instrumentation and non-intuitive signals. Herein, we have controllably and proportionately integrated molybdenum disulfide (MoS2 ) with titanium dioxide (TiO2 ) to prepare MoS2 @TiO2 nanocomposites (MoS2 @TiO2 NCs) via a facile synthesis method. MoS2 @TiO2 NCs with a certain reactant mass ratio have shown a significant enhancement in peroxidase-like activity with superiority of the nanocomposite structure compared to single MoS2 or natural enzyme. The method for catalyzing the decomposition of H2 O2 by MoS2 @TiO2 NCs and competition for hydroxyl radicals (˙OH) between the chromogenic agent and DA enable a sensitive, specific, and colorimetric DA analysis with a low detection limit of 0.194 μM and a wide linear detection range (0.8 to 100 μM). Because of the favorable detection performance, we were encouraged to explore and finally realize the visual detection of cellular DA secretion that is stimulated in a High-K + neurocyte environment. Collectively, this method will provide a promising strategy for basic research in neuroscience with its portable, sensitive, and naked-eye detectable performance.